VD_FINDINFO HC / 2010 / 206 vom 9. Februar 2010 - VD Tribunal cantonal (2010)
DIVORCE, AUTORITÉ PARENTALE | 133 al. 1 CC, 133 al. 2 CC, 133 al. 3 CC, 133 CC, 145 al. 1 CC, 451 ch. 2 CPC, 452 al. 1ter CPC, 452 al. 2 CPC